2016
DOI: 10.1021/acscatal.6b02735
|View full text |Cite
|
Sign up to set email alerts
|

On the Preferred Active Sites of Promoted MoS2 for Hydrodesulfurization with Minimal Organonitrogen Inhibition

Abstract: Hydrodesulfurization is a process to produce ultralow-sulfur diesel fuel. Although promoted molybdenum sulfide (MoS2) catalysts have been used industrially for several decades, the active site requirements for selective hydrodesulfurization of organosulfur compounds with minimal inhibition by organonitrogen constituents of a real gasoil feed has not been resolved. Using molecular binding energy descriptors derived from plane wave density functional theory calculations for comparative adsorption of organosulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 91 publications
(139 reference statements)
8
71
0
Order By: Relevance
“…Liu et al [215] demonstrated that for a MoS 2 /NiMo catalyst, the higher the number of MoS 2 slabs being stacked, the better the hydrodesulfurization selectivity for DBT. Additionally, Rangarajan et al [216] studied the preferred active sites of a metal-promoted MoS 2 and found that organosulfur and organonitrogen compounds bind weaker on sites with exposed metal on the corner and the sulphur edge of MoS 2 . Hydrodesulfurization of DBT by various morphologies of MoS 2 catalyst was also studied by Tye and Smith [217].…”
Section: Fuel Hydrodesulfurizationmentioning
confidence: 99%
“…Liu et al [215] demonstrated that for a MoS 2 /NiMo catalyst, the higher the number of MoS 2 slabs being stacked, the better the hydrodesulfurization selectivity for DBT. Additionally, Rangarajan et al [216] studied the preferred active sites of a metal-promoted MoS 2 and found that organosulfur and organonitrogen compounds bind weaker on sites with exposed metal on the corner and the sulphur edge of MoS 2 . Hydrodesulfurization of DBT by various morphologies of MoS 2 catalyst was also studied by Tye and Smith [217].…”
Section: Fuel Hydrodesulfurizationmentioning
confidence: 99%
“…Under typical sulfidation conditions, nickel atoms might replace the molybdenum atoms from the Mo-edge to form the so-called NiMoS phase and, hence, promote the formation of CUS at the edges and corners due to the reduction of the sulfur binding energy. 75,76 The desulfurization of DBTs via DDS preferably takes place on vacancies at corner sites via perpendicular adsorption through the sulfur atom. 20,24,75,77 On the other hand, the nature of the sites for the HYD pathway is yet unclarified.…”
Section: Nature Of the Active Sitesmentioning
confidence: 99%
“…75,76 The desulfurization of DBTs via DDS preferably takes place on vacancies at corner sites via perpendicular adsorption through the sulfur atom. 20,24,75,77 On the other hand, the nature of the sites for the HYD pathway is yet unclarified. TopsĂže and coworkers [22][23][24]73 , based on scanning tunneling microscopy (STM) images of the top of MoS2 and CoMoS slabs,…”
Section: Nature Of the Active Sitesmentioning
confidence: 99%
“…The air pollution is one of the main problems that the governments around the world have been concerned to mitigate in recent decades. The harmful gases found in the atmosphere are the product of the generation of energy through the combustion of hydrocarbons [1][2][3]. However, the hydrocarbons will continue to be used as the main source of energy in the next decades [4]; thus, it represents an environmental problem.…”
Section: Introductionmentioning
confidence: 99%